Deep learning models for brain machine interfaces - Bozhkov, Lachezar; Georgieva, Petia (Annals of mathematics and artificial intelligence, 2020)
Deep Learning methods have been rising in popularity in the past few years, and are now used as a fundamental component in various application domains such as computer vision, natural language processing, bioinformatics. Supervised learning with Convolutional Neural Networks has become the state of the art approach in many image related works. However, despite the great success of deep learning methods in other areas they remain relatively unexplored in the brain imaging field. In this paper we make an overview of recent achievements of Deep Learning to automatically extract features from brain signals that enable building Brain-Machine Interfaces (BMI). Major challenge in the BMI research is to find common subject-independent neural signatures due to the high brain data variability across multiple subjects. To address this problem we propose a Deep Neural Autoencoder with sparsity constraint as a promising approach to extract hidden features from Electroencephalogram data (in-dept feature learning) and build a subject-independent noninvasive BMI in the affective neuro computing framework. Future direction for research are also outlined.